Situation Report: Poland, 27 November 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Full Week in Poland Personnel Changes in Party and Government / by Ewa Celt The Authorities Announce Proposals for Price Increases Taming the Intelligentsia: The Legal Profession / by Ewa Celt Passport Regulations and Allied Problems Sundry Items